Thermal radiation, chemical reaction, viscous and joule dissipation effects on MHD flow embedded in a porous medium - Zigta, Binyam (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is presented to study the effects of thermal radiation, chemical reaction, viscous and Joule dissipation on MHD free convection flow between a pair of infinite vertical Couette channel walls embedded in a porous medium. The fluid flows by a strong transverse magnetic field imposed perpendicularly to the channel wall on the assumption of a small magnetic Reynolds number.
Keywords: thermal radiation; chemical reaction; Joule dissipation; viscous dissipation; porous medium